Analyzing the physics of radio telescopes and radio astronomy - Yeap, Kim Ho; Hirasawa, Kazuhiro, 1941- (Advances in environmental engineering and green technologies (AEEGT) book series., 2020)
"This book examines the underlying operational principles of radio telescopes and illustrates how signals from the cosmic sources are detected and analyzed. It also expounds on the physics of the celestial objects detected by radio telescopes"--